2008
DOI: 10.1080/14992020802294040
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention in South Africa: Moving beyond hearing screening

Abstract: Since little information is available on the outcome of early hearing intervention programs in South Africa, this article examines data on infants and families registered with a family-centred, home-based intervention program (HI HOPES) over a 12-month period in order to track the effectiveness of the holistic unbiased support to families of infants and toddlers with a hearing-loss. The aim of HI HOPES, which is based on the SKI-HI model of early intervention in the USA, is to ensure that families are enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The program adopts an unbiased informative approach emphasizing informed choice by parents and serves infants in the category of birth to 3 years of age in both private and public health sectors at no cost to families. Initial findings for the program indicate significant improvements in language development (expressive and receptive) for the infants receiving services [31].…”
Section: Early Intervention Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The program adopts an unbiased informative approach emphasizing informed choice by parents and serves infants in the category of birth to 3 years of age in both private and public health sectors at no cost to families. Initial findings for the program indicate significant improvements in language development (expressive and receptive) for the infants receiving services [31].…”
Section: Early Intervention Servicesmentioning
confidence: 99%
“…It is only recently that the first home-based family-centred early intervention program was instituted. The HI HOPES (Home InterventionHearing and language Opportunities Parent Education Services) home-based intervention program was launched in the Gauteng province in 2006 and since this time has begun to expand services into several other provinces as well [31,32]. The program adopts an unbiased informative approach emphasizing informed choice by parents and serves infants in the category of birth to 3 years of age in both private and public health sectors at no cost to families.…”
Section: Early Intervention Servicesmentioning
confidence: 99%
“…A disabling hearing loss is usually described as one above 30 or 40dB [2,16], however research and experience has shown that if it remains undetected all hearing loss (including minimal and unilateral hearing losses) can have detrimental consequences [17][18][19][20]. These consequences include delays in language development, cognitive development and socioemotional development [6,[21][22][23][24] which may result in persistent language delays of 2-4 years [25]. These delays then have far reaching ramifications for academic, employment and societal integration [25,26], particularly in developing countries.…”
Section: Hearing Loss and Its Impactmentioning
confidence: 99%
“…In a survey on the reasons for not using needed health facilities in two Indian states, 52.3% of respondents indicated that no healthcare facility in the area was available (112). Other countries lack rehabilitation services that have proven effective at reducing longterm costs, such as early intervention for children under the age of 5 (5,(113)(114)(115). A study of users of community-based rehabilitation (CBR) in Ghana, Guyana, and Nepal showed limited impact on physical well-being because CBR workers had difficulties providing physical rehabilitation, assistive devices, and referral services (116).…”
Section: Addressing Barriers To Rehabilitationmentioning
confidence: 99%